Influence of the Servant Leadership, Organizational Culture and Employee Motivation on Work Performance - Peter Yumte; Yohanis Rante; Josephus Ronsumbre; Westim Ratang (Journal of Social and Development Sciences, 2017)
Servant Leadership, Organizational Culture and Work Motivation is a very important variable that to Achieve the performance of employees / employee better. Performance is an aspect to measure the quality and quantity of individuals in an organization. Employee performance affects the achievement of organizational goals. The dynamics of working in organization need individuals who are effective and efficient in their work, both personal and team. The purpose of this study is: to analyze the effect of servant leadership to employee performance Mimika District Hospital, to analyze the influence of organizational culture on employee performance Mimika District Hospital, To analyze the effect of work motivation on employee performance Mimika District Hospital. This study uses a saturated or census sampling methods and the data used in this research is the primary data is in the form of a questionnaire. This study used a sample of as many as 198 people. The analysis technique used in this study is the technique of path analysis (path analysis) using the program Structural Equation Modeling (SEM) with the help of program Analysis Moment Structures (AMOS) and qualitative analysis using interactive methods .. Based on test validity and reliability by using factor analysis shows, the instruments used in the study are valid and reliable. The results Showed that (1) Effect of servant leadership to employee performance Mimika district hospitals have a significant effect, in the which the servant leadership Directly Contribute to or influenced by 1.6% on employee performance and influence indirectly because of his association with two other independent variables by 1.2% and by 2.5% job satisfaction. The influence of organizational culture on employee performance Mimika hospitals have a significant effect of the which contributes greatly to the performance of employees. The effect of work motivation on employee performance hospitals Mimika has a significant influence on employee performance Mimika district hospitals, where the higher work motivation will improve employee performance.